Low metal content polyolefin filter membrane

By adopting specific polyesterene membrane materials and controlling the content of metal elements in it, the liquid contamination problem caused by the residue of metal catalysts in the filter membrane materials in the prior art is solved, and a high-purity liquid filtration effect is achieved, which is particularly suitable for industries such as semiconductor manufacturing.

JP2025060665AInactive Publication Date: 2025-04-10ENTEGRIS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024216131
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-10-30
Filing Date
2024-12-11
Publication Date
2025-04-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the filter membrane materials used for liquid filtration often contain metal catalyst residues, resulting in metal ion contamination in the liquid after filtration. Especially in industries such as semiconductor manufacturing, these pollutants can seriously affect equipment performance and product quality.

Method used

The specific polyesterolefin film material is used to selectively control the content of metal elements in it to ensure that the total amount of titanium, aluminum, iron, zinc and magnesium is less than 4 ppm, and the metal catalyst residues are reduced or removed by using processes such as the ring opening element polymerization reaction (ROMP) and hydrogenation reaction of Ru II catalyst.

Benefits of technology

It significantly reduces the concentration of metal ions in the filtrate and improves the purity of liquid filtration. It is especially suitable for industries such as semiconductor manufacturing that require extremely low metal ion pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060665000001_ABST
    Figure 2025060665000001_ABST
Patent Text Reader

Abstract

To provide certain polyolefinic membranes which are useful as components of filters for liquid purification, wherein, advantageously, the filter membranes of the present disclosure possess greatly reduced concentrations of certain trace metals, thus making them particularly useful in the filtration of liquids used in the fabrication of microelectronic devices.SOLUTION: The present disclosure provides a filter membrane comprising a polyolefin, wherein the polyolefin has less than about 4 ppm in total of metals selected from titanium, aluminum, iron, zinc, and magnesium.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to filter membranes comprising polyolefins that are essentially free of metal contaminants typically found in polymer and filter containing such membranes. [Background technology]

[0002] Filter products are essential tools in modern industry used to remove unwanted materials from useful fluid streams. Useful fluids that are treated using filters include water, liquid industrial solvents and process fluids, industrial gases used in manufacturing or processing (e.g., in semiconductor manufacturing), and liquids with medical or pharmaceutical applications. Undesirable materials that are removed from fluids include impurities and contaminants such as particles, microorganisms, and dissolved chemical species. Specific examples of filter applications include their use with liquid materials for semiconductor and microelectronic device manufacturing.

[0003] To perform the filtration function, the filter may include a filter membrane, which serves to remove unwanted materials from the fluid passing through the filter membrane. The filter membrane may be in the form of a flat sheet, rolled (e.g., spiral), flat, pleated, or disk-shaped, as appropriate. Alternatively, the filter membrane may be in the form of hollow fibers. The filter membrane may be contained or otherwise supported within a housing such that the fluid being filtered enters through a filtration inlet and must pass through the filter membrane before passing through a filtration outlet.

[0004] Filter membranes can be constructed of porous structures with an average pore size that can be selected based on the use of the filter, i.e., the type of filtration performed by the filter. Typical pore sizes are in the micrometer or submicrometer range, for example, from about 0.001 micrometer to about 10 micrometers. Membranes with an average pore size of about 0.001 to about 0.05 micrometers are sometimes classified as ultrafilter membranes. Membranes with a pore size of about 0.05 to 10 micrometers are sometimes called microporous membranes.

[0005] Filter membranes with pore sizes in the micrometer or sub-micrometer range can be effective in removing undesirable materials from a fluid stream by either sieving or non-sieving mechanisms, or both. Sieving mechanisms are modes of filtration that remove particles from a liquid stream by mechanically retaining them on the surface of the filter membrane, which acts to mechanically interfere with the movement of the particles, retaining them within the filter and mechanically preventing the flow of particles through the filter. Typically, the particles can be larger than the pores of the filter. "Non-sieving" filtration mechanisms are modes of filtration in which the filter membrane retains suspended particles or dissolved materials contained in the fluid stream passing through the filter membrane in a manner that is not necessarily mechanical, including, for example, electrostatic mechanisms in which particulates or dissolved impurities are electrostatically attracted and retained on the filter surface and removed from the fluid stream, the particles may be dissolved or solid with a particle size smaller than the pores of the filter material.

[0006] Many such filter membranes are composed of polyolefins, which are generally prepared using various metal-containing catalysts. For example, certain polyolefins, such as polyethylene, are prepared using Ziegler-Natta catalysts and may contain metals such as titanium, aluminum, and magnesium. Other catalysts may contain chromium or silicon. Such catalysts are therefore present in small but potentially harmful amounts in filter media prepared from such polyolefins. If used as is, the filter media may leach these metals when being used to filter liquid compositions such as solvents. Thus, these filter media are typically washed to remove such metal contaminants at or near the surface of the polyolefin material. Thus, the metals not removed during such processes remain entrapped in the polymer matrix and may therefore leach under operating conditions. Removal of ionic materials, such as dissolved metal cations, from solution is important in many industries, such as the microelectronics industry, where very low concentrations of cationic metal contaminants can ultimately adversely affect the quality and performance of microprocessors and memory devices. The ability to prepare positive and negative photoresists with low levels of metal ion contaminants, or to deliver isopropyl alcohol for use in Maragoni drying for wafer cleaning with parts per billion or parts per trillion levels of metal ion contaminants, is highly desirable and are just two examples of the need for contamination control in semiconductor manufacturing. Thus, there remains a need for improved methods of filtering liquid compositions in which the presence of such metal ions is reduced or effectively eliminated. Summary of the Invention

[0007] In summary, the present disclosure provides certain polyolefin membranes useful as components of filters for liquid purification and / or filtration. In one embodiment, the polyolefin is selected from polyethylene and copolymers such as polyethylene and polyethylene-co-polybutylene. Advantageously, the filter membranes of the present disclosure are particularly useful for filtering liquids used in the manufacture of microelectronic devices due to the significantly reduced concentration of certain trace metals. In one aspect, the present disclosure provides a filter membrane comprising a polyolefin, wherein the total amount of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 4 ppm as determined by the MARS6 Microwave Acid Digestion Method Note Compendium.

[0008] The present disclosure may be more fully understood in consideration of the following description of various exemplary embodiments in conjunction with the accompanying drawings. [Brief description of the drawings]

[0009] [Figure 1] 1 illustrates (schematically and not necessarily to scale) an example of a filter product as described herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] While the present disclosure is susceptible to various modifications and alternative forms, specifics thereof have been shown by way of example in the drawings and will be described in detail. It should be understood, however, that the intention is not to limit aspects of the disclosure to the particular exemplary embodiments described. On the contrary, the intention is to cover all modifications, equivalents, and alternatives falling within the spirit and scope of the disclosure.

[0011] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the content clearly dictates otherwise. As used in this specification and the appended claims, the term "or" is generally used in its sense including "and / or" unless the content clearly dictates otherwise.

[0012] The term "about" generally refers to a range of numbers that are considered equivalent to the recited value (e.g., having the same function or result). In many cases, the term "about" may include numbers that are rounded to the nearest significant figure.

[0013] Numerical ranges expressed using endpoints include all numbers subsumed within that range (eg, 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, and 5).

[0014] The amount of trace metals present in polyolefins is measured using the method described in "MARS 6 Microwave Acid Digestion Method Note Compendium", Microwave Digestion of polyethylene-High density p 511. CEM corporation. October 1, 2019. Website: https: / / cem.com / media / contenttype / media / literature / MetNote_MARS6_Compendium_2.pdf. After microwave digestion, samples were diluted approximately 50-fold with deionized (DI) water and tested for metal concentrations using inductively coupled plasma mass spectrometry (ICP-MS).

[0015] In a first aspect, the present disclosure provides a filter membrane comprising a polyolefin, wherein the total amount of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 4 ppm as determined by the MARS6 Microwave Acid Digestion Method Note Compendium. The total level of metals is based on μg of total metals per gram of polyolefin resin. In other embodiments, the polyolefin has a total of less than about 3.5 ppm, or less than about 3 ppm, or less than about 2 ppm, or less than about 1 ppm of metals selected from titanium, aluminum, iron, zinc, and magnesium.

[0016] In another embodiment, the polyolefin has less than about 1 ppm ruthenium. In one embodiment, the sum of titanium, aluminum, silicon, chromium, and magnesium in the polyolefin is greater than 0.1 ppm, and ruthenium is greater than 0.1 ppm and less than the amounts stated above.

[0017] In one embodiment, the polyolefin is selected from polyethylene and polyethylene copolymers. Exemplary polyolefins include polyethylene and copolymers such as polyethylene-co-polybutylene. The physical properties of copolymers such as polyethylene-co-polybutylene are similar to commercially available polyethylene. In one embodiment, the polyolefin is polyethylene. In another embodiment, the polyethylene-co-polybutylene has a number average molecular weight of about 330,000 to about 2,200,000 Daltons. In another embodiment, the polyethylene and polyethylene-co-polybutylene have a number average molecular weight of about 700,000 to about 1,500,000 Daltons. In another embodiment, the polyolefin is ultra-high molecular weight polyethylene.

[0018] The filter membrane of the first embodiment can be composed of polyethylene that can be prepared by the ring-opening metathesis polymerization (ROMP) reaction of 1-octene with a Ruthenium II catalyst, for example according to the following scheme: TIFF2025060665000002.tif23170

[0019] In the above reaction, the Ru II catalyst is utilized in a ring-opening metathesis polymerization (ROMP) reaction to provide an unsaturated polymer of formula (A) (i.e., polyethylene). The reaction is generally carried out in a non-polar aprotic solvent such as hexane, dichloromethane, chloroform, toluene, diethyl ether, ethyl acetate, etc., and can be carried out at room temperature or slightly elevated temperatures, for example, from about 23° C. to about 70° C. In one embodiment, the Ru II catalyst has functional groups that render the catalyst soluble or water-dispersible, thus facilitating its removal during work-up of the product using conventional aqueous extraction. Such functional groups include, for example, ammonium groups, quaternary ammonium groups, amines, polyalkylene glycols, etc., that allow for effective removal of the catalyst from an organic solution of the polymer of formula (A) by aqueous solutions (acidic or basic pH), sequential precipitation, Soxhlet extraction, or adsorption onto silica, or adsorption onto ion exchange or chelating resins. Alternatively, the ruthenium II catalyst may be tethered to a solid support as an alternative means for separating the catalyst from the reaction product mixture, thus reducing or effectively eliminating ruthenium contamination of the resulting polyolefin.

[0020] Examples of suitable ruthenium II catalysts include those known as Grubbs catalysts and Hoveyda-Grubbs second generation catalysts. Suitable metathesis catalysts include those available from Apeiron Synthesis. Specific catalysts include i. (1,3-bis(2,6-diisopropylphenyl)-4-((4-ethyl-4-methylpiperazin-1-ium-1-yl)methyl)imidazolidin-2-ylidene)(2-isopropoxybenzylidene)ruthenium(II) chloride dihydrate; ("FixCat"); ii. (1,3-Dimesityl-4-((trimethylammonio)methyl)imidazolidin-2-ylidene)dichloro(2-isopropoxybenzylidene)ruthenium(II) chloride; ("StickyCat Cl"); iii. (4-((4-ethyl-4-methylpiperazin-1-ium-1-yl)methyl)-1,3-dimesitylimidazolidin-2-ylidene)dichloro(2-isopropoxybenzylidene)ruthenium(II) chloride ("AquaMet") iv. (1,3-dimesityl-4-((trimethylammonio)methyl)imidazolidin-2-ylidene)dichloro(2-isopropoxybenzylidene)ruthenium(II) hexafluorophosphate; ("StickyCat PF6"); and v. (1,3-Dimesityl-4-((trimethylammonio)methyl)imidazolidin-2-ylidene)dichloro(2-isopropoxybenzylidene)ruthenium(II) tetrafluoroborate; ("StickyCat BF4") Includes:

[0021] The reaction is typically carried out for a period of 0.3 to 4 hours, followed by chain scission using a vinyl ether such as ethyl vinyl ether, ethylene glycol vinyl ether, di(ethylene glycol) vinyl ether, or di(ethylene glycol) divinyl ether.

[0022] The purified solution of the unsaturated polymer of formula (A) may then be reduced using a hydrazine- or hydrazide-type reducing agent, such as p-toluenesulfonylhydrazide, in the presence of an amine, such as tripropylamine, to provide a saturated polyethylene compound represented by formula (B). TIFF2025060665000003.tif21170

[0023] Thus, in another aspect, the present disclosure provides the membrane as described above, wherein the polyolefin comprises: A. cis- or trans-cyclooctene is contacted with a Ru II catalyst, followed by B. Removal or extraction of Ru II catalyst, followed by C. Hydrogenation with hydrazine or hydrazide type reducing agents It is prepared by

[0024] Alternatively, the polyolefin of the first aspect may be prepared by reducing commercially available polybutadiene (CAS number 9003-17-2). Such reduction (i.e., hydrogenation) may be accomplished by using a hydrazine- or hydrazide-type reducing agent, such as p-toluenesulfonylhydrazide (available from Sigma-Aldrich, CAS number 576-35-8), in the presence of an amine, such as tributylamine. Other suitable reducing agents include benzenesulfonylhydrazide; 2,4,6-triisopropylbenzenesulfonylhydrazide; 2,4,6-trimethylbenzenesulfonohydrazide; N,N'-bis(p-toluenesulfonyl)hydrazine, and the like. Thus, a compound of formula (C) may be prepared according to the following scheme: The compound of formula (C) is called polyethylene-co-polybutylene. TIFF2025060665000004.tif27170

[0025] Thus, in another aspect, the present disclosure provides the membrane, wherein the polyolefin is prepared by contacting polybutadiene with hydrogen in the presence of a hydrazide- or hydrazine-type reducing agent.

[0026] The polyolefins of formula (B) and (C) in one embodiment have a number molecular weight (M) of about 330 K Daltons to about 2.2 M Daltons, or about 700 K Daltons to about 1.5 M Daltons, or about 1.1 M Daltons. n ).

[0027] The polyolefins of formula (B) and (C) can then be utilized to manufacture filter membranes for use in various filter structures. A suitable process for preparing the porous filter membranes as described can be an extrusion melt casting process or a method sometimes referred to as "thermally induced liquid-liquid phase separation". In this type of process, a polymer is dissolved at high temperature ("extrusion temperature") in a combination of two or more solvents to form a heated polymer solution that can be processed and molded, for example, by an extruder. The heated polymer solution can be passed through an extruder and an extrusion die to be molded, such as in the form of a sheet-like membrane. The heated polymer solution passes through a die and is distributed onto a molding surface that is at a temperature much lower than the extrusion temperature, i.e., a "cooling temperature". When the extruded heated polymer solution contacts the cold molding surface, the polymer and solvent of the heated polymer solution undergo one or more phase separations to form the polymer into the porous filter membrane described herein. An example of a comparable process for manufacturing a porous polymer molding material is described, for example, in U.S. Patent No. 6,497,752, which is incorporated herein by reference in its entirety.

[0028] The filter membrane as described may be contained within a larger filter structure, such as a filter cartridge used in a multi-layer filter assembly or filtration system. The filtration system places the filter membrane in a filtration housing, for example as part of a multi-layer filtration assembly or as part of a filter cartridge, exposing the filter membrane to a flow path of the medical fluid so that the filter membrane removes a certain amount of impurities or contaminants from the medical fluid, and passes at least a portion of the flow of the medical fluid through the filter membrane. The structure of the multi-layer filter assembly or filter cartridge may include one or more of a variety of additional materials and structures that support the composite filter membrane within the filter assembly or filter cartridge to allow the fluid to flow from the filter inlet through the composite membrane (including the filter layer) through the filter outlet, thereby passing the composite filter membrane as it passes through the filter. The filter membrane supported by the filter assembly or filter cartridge may be any useful shape, such as a pleated cylinder, a cylindrical pad, a cylindrical sheet without one or more pleats (flat), a pleated sheet, among others.

[0029] An example of a filter structure that includes a filter membrane in the form of a pleated cylinder can be prepared to include the following components: a rigid or semi-rigid core that supports the pleated cylindrical coated filter membrane at the inner opening of the pleated cylindrical coated filter membrane; a rigid or semi-rigid cage that supports or surrounds the outside of the pleated cylindrical coated filter membrane at the outside of the filter membrane; an optional end piece or "pack" that is located at each of the two opposite ends of the pleated cylindrical coated filter membrane; and a filter housing that includes an inlet and an outlet, any of which may be included in the filter structure, but may not be required. The filter housing can have any useful and desired size, shape, and material, and can preferably be made of a suitable polymeric material.

[0030] The following detailed description should be read with reference to the drawings, in which like elements in different drawings are numbered the same. The detailed description and drawings, which are not necessarily to scale, depict exemplary embodiments and are not intended to limit the scope of the invention. The illustrated exemplary embodiments are intended as examples only. Selected features of any exemplary embodiment may be incorporated in additional embodiments, unless expressly stated to the contrary.

[0031] As an example, FIG. 1 shows a filter element 30 that is a product of a pleated cylindrical component 10 and an end piece 22, as well as other optional components. The cylindrical component 10 includes a filter membrane 12 and is pleated, as described herein. The end piece 22 is attached (e.g., "potted") to one end of the cylindrical filter element 10. The end piece 22 may preferably be made of a melt-processable polymeric material. A core (not shown) may be placed in the interior opening 24 of the pleated cylindrical component 10, and a cage (not shown) may be placed around the outside of the pleated cylindrical component 10. A second end piece (not shown) may be attached ("potted") to a second end of the pleated cylindrical component 30. The resulting pleated cylindrical component 30 with two opposing potted ends and the optional core and cage may then be placed in a filter housing that includes an inlet and an outlet, and is configured such that all of the fluid entering the inlet must pass through the filtration membrane 12 before exiting the filter at the outlet. EXAMPLES

[0032] material: All materials were used as received. Dichloromethane 99.6%, cis-cyclooctene 95% from Alfa Aesar. Chloroform 99.8% from Merck KgaA. (4-((4-ethyl-4-methylpiperazin-1-ium-1-yl)methyl)-1,3-dimesitylimidazolidin-2-ylidene)dichloro(2-isopropoxybenzylidene)ruthenium(II) chloride (AquaMet) >99%, ((1,3-bis-(2,4,6-trimethylphenyl)-2-imidazolidinylidene)dichloro(o-isopropoxyphenylmethylene)ruthenium, Hoveyda-Grubbs from Sigma Aldrich. Catalyst® M72 >97%, cis and trans decahydronaphthalene mixture, anhydrous >99%, 1,4-bis(3-isocyanopropyl)piperazine (SnatchCat) >95%, 2,6-di-tert-butyl-4-methylphenol >99.0%, ethyl vinyl ether, 99%, ethylene glycol vinyl ether, 97%, hydrochloric acid (HCl) 37%, p-toluenesulfonyl hydrazide >97%, tripropylamine >98%, xylene >98.5%. Isopropyl alcohol (IPA) gigabit grade KMG from VWR, hexane 98.5%. ([1,3-bis(2,4,6-trimethylphenyl)-4-[(trimethylammonio)methyl]imidazolidin-2-ylidene]-(2-i-propoxybenzylidene)dichlororuthenium(II) chloride) from Strem Chemicals (Stickycat Cl)>99%. Polybutadiene from Polysource (P10053-Bd, M n= 1200 kDaltons, D = 1.18). Tetramethylammonium hydroxide (25% in H2O) from JT Baker. Silica gel for column chromatography 40um-60um, average pore size 60Å from Acros organics. SiliaMetS thiol (SH) Metal Scavenger (R51030B) (pore size 60Å) from Silicycle. Puromet MTS9100 (amide oxime) from Purolite and NRW160 resin from Purolite. Cellulose filter paper No 42 ashless circle 90mm from Whatman. (Trademark) PTFE based beakers, separating funnels and vials.

[0033] Analysis method: The samples were analyzed according to the method described in "MARS 6 Microwave Acid Digestion Method Note Compendium", Microwave Digestion of polyethylene-High density p 511. CEM corporation. October 1, 2019. Website: https: / / cem.com / media / contenttype / media / literature / MetNote_MARS6_Compendium_2.pdf.

[0034] After microwave digestion, samples were diluted approximately 50-fold with deionized (DI) water and tested for metal concentrations using inductively coupled plasma mass spectrometry (ICP-MS).

[0035] Polymer molecular weights were determined using gel permeation chromatography (GPC) coupled with an Agilent 1260 refractive index detector. Data acquisition and handling was performed using Jordi GPC software. Data were obtained under the following conditions: Solvent: Chloroform. Column: Jordi Resolve DVB MB+500Å, 300x7.8mm, calibrated with polystyrene standards 6.57M, 3.152M, 885K, 479.2K, 194.5K, 75.05K, 22.29K, 10.33K, 4.88K, 1.21K, 580&162Da. Flow rate: 1.0mL / min.

[0036] The sample was measured using a Bruker 75MHz 13 The samples were analyzed by C melt-state NMR at 150 °C with a MAS frequency of 2.5 kHz. The duration of each experiment was 18 h. The exponential window function of the spectrum was 3 Hz (S / N>1000).

[0037] Elemental analyses were determined using a Perkin-Elmer 2400 equipped with an oxygen accessory kit.

[0038] Melting temperatures were determined using a Perkin Elmer Diamond Differential Scanning Calorimeter (DSC).

[0039] Example 1: This example demonstrates the synthesis of polyoctene and the expected M n =2200kDaltons.

[0040] In a representative experiment, a solution of 11.8 mL of cis-cyclooctene in 180 mL of chloroform was added dropwise to a solution of 3.3 mg of Stickycat Cl in 3 mL of chloroform over a period of 60 min.

[0041] Then, 100 mL of chloroform was added and the solution was heated for 4 hours at 40° C. Then, 2.5 mL of ethyl vinyl ether was added in one portion and stirred at 40° C. for 0.5 hours.

[0042] The organic phase was then extracted five times with 50 mL of acid solution HCl (10%) made from 68.2 mL of HCl (37%) in 181 mL of DI water. For each extraction, 0.2 mL of ethyl vinyl ether was added to the organic phase and the solution was stirred for 20 min after each extraction.

[0043] After extraction, the solution was poured into 200 mL of isopropyl alcohol. A white polymer precipitated. The mother liquor was decanted and the polymer was dried in a convection oven at room temperature for 16 hours (9.90 g, 99.0% yield). Metal concentrations were determined using microwave digestion and ICP-MS. Al=0.0ppm, Mg=0.0ppm, Ti=0.0ppm, Zn=0.0ppm, Fe=0.0ppm, Ru=5.4ppm. Therefore, the sum of titanium, aluminum, iron, zinc, and magnesium is 0.0 ppm.

[0044] A subsequent run under the same conditions yielded 5.6 g of polymer after drying, a yield of 56.0%. Metal concentrations were determined using microwave digestion and ICP-MS: Al=0.00 ppm, Mg=0.00 ppm, Ti=0.28 ppm, Zn=0.00 ppm, Fe=0.05 ppm, Ru=10.39 ppm. The sum of titanium, aluminum, iron, zinc, and magnesium is therefore 0.33 ppm.

[0045] Example 2: This example demonstrates the synthesis of polyoctene with purification using successive precipitation, and shows the expected M n =2200kDaltons.

[0046] In a representative experiment, a solution of 11.8 mL of cis-cyclooctene in 180 mL of chloroform was added dropwise to a solution of 3.3 mg of Stickycat Cl in 3 mL of chloroform over a period of 60 min.

[0047] Then, 100 mL of chloroform was added and the solution was heated for 4 hours at 40° C. Then, 2.5 mL of ethyl vinyl ether was added in one portion and stirred at 40° C. for 0.5 hours.

[0048] The organic solution was poured into 300 mL of IPA, causing the white polymer to precipitate.

[0049] The liquid was decanted and the white polymer was dried in a convection oven at room temperature for 10 hours. The polymer was then redissolved in 180 mL of dichloromethane at 30° C. and reprecipitated three times using the indicated amount of IPA.

[0050] The polymer was then dried in a convection oven at room temperature for 16 hours (9.20 g, 92% yield). Metal concentrations were determined using microwave digestion and ICP-MS: Al=0.0 ppm, Mg=0.0 ppm, Ti=0.4 ppm, Zn=0.1 ppm, Fe=0.1 ppm, Ru=0.6 ppm. The sum of titanium, aluminum, iron, zinc, and magnesium is therefore 0.6 ppm.

[0051] In a subsequent run under the same conditions, the polymer after drying was 4.2 g, a yield of 42%. Metal concentrations were determined using microwave digestion and ICP-MS. After the first precipitation, the metal concentrations were Al=0.00 ppm, Mg=0.00 ppm, Ti=0.00 ppm, Zn=0.00 ppm, Fe=11.46 ppm, Ru=3.88 ppm. After the second precipitation, the metal concentrations were Al=0.00 ppm, Mg=0.00 ppm, Ti=0.00 ppm, Zn=0.00 ppm, Fe=0.00 ppm, Ru=2.98 ppm. The sum of titanium, aluminum, iron, zinc, and magnesium is therefore 0.00 ppm.

[0052] Example 3: This example demonstrates the synthesis of polyoctene and the expected M n =330kDaltons.

[0053] In a representative experiment, a solution of 177 mL of cis-cyclooctene in 2950 mL of chloroform was added dropwise to a solution of 333 mg of Stickycat Cl in 43 mL of chloroform over a period of 35 min.

[0054] The solution was heated to 40° C. for 6 hours. Then, 8 mL of ethylene glycol vinyl ether was added in one portion and stirred at room temperature for 4 hours.

[0055] The viscous solution was extracted five times with 3 L of DI water. 8 mL of ethylene glycol vinyl ether was added to the organic phase and the solution was stirred for 20 minutes after each extraction.

[0056] After extraction, the solution was poured into 6 L of IPA. A white polymer precipitated. The mother liquor was decanted and the polymer was dried in a convection oven at room temperature for 16 hours (146 g, 97% yield). Metal concentrations were determined using microwave digestion and ICP-MS: Al=2.7 ppm, Mg=0.3 ppm, Ti=0.0 ppm, Zn=0.3 ppm, Fe=0.0 ppm, Ru=42.1 ppm. The sum of titanium, aluminum, iron, zinc, and magnesium is therefore 3.3 ppm.

[0057] In a subsequent run under the same conditions, the polymer after drying weighed 129 g, a yield of 86%. GPC (Mn=132.2 kDaltons, Mw=202.8 kDaltons, D=1.5).

[0058] Example 4: This example demonstrates the synthesis of polyoctene and the expected M n =1100kDaltons.

[0059] In a representative experiment, a solution of 5.9 mL of cis-cyclooctene in 50 mL of dichloromethane was added dropwise to a solution of 3.5 mg of Aquamet in 2 mL of dichloromethane over a period of 4 minutes.

[0060] The solution was heated to 36° C. for 30 minutes to give a viscous solution. 200 mL of hexane was then added and heated to 50° C. for 3 hours. Then, 2 mL of ethylene glycol vinyl ether was added in one portion and stirred at room temperature for 4 hours.

[0061] The organic solution was poured into 200 mL of IPA, causing the white polymer to precipitate.

[0062] The liquid was decanted and the white polymer was dried in a convection oven at room temperature for 10 hours. The polymer was then redissolved in 300 mL of dichloromethane at 30° C.

[0063] The viscous solution was extracted five times with 20 mL of DI water. After extraction, the solution was poured into 200 mL of IPA. A white to light brown polymer precipitated. The mother liquor was decanted and the polymer was dried in a convection oven at room temperature for 16 hours (4.5 g, 90% yield). Metal concentrations were determined using microwave digestion and ICP-MS: Al=0.9 ppm, Mg=0.7 ppm, Ti=0.0 ppm, Zn=0.0 ppm, Fe=0.0 ppm, Ru=2.4 ppm. The sum of titanium, aluminum, iron, zinc, and magnesium is therefore 1.6 ppm.

[0064] A subsequent run under the same conditions yielded 3.5 g of polymer after drying, a yield of 70%. Metal concentrations were determined using microwave digestion and ICP-MS to be Al=0.00 ppm, Mg=0.00 ppm, Ti=0.00 ppm, Zn=0.00 ppm, Fe=0.00 ppm, Ru=11.62 ppm. The sum of titanium, aluminum, iron, zinc, and magnesium is therefore 0.00 ppm.

[0065] Example 5: (Prophetic) This example demonstrates the synthesis of polyoctene with purification using silica gel adsorption, and shows the expected M n =5500kDaltons.

[0066] In a typical experiment, a solution of 11.8 mL of cis-cyclooctene in 170 mL of chloroform is added dropwise to a solution of 1.3 mg of Stickycat Cl in 3 mL of chloroform over a period of 60 min.

[0067] Then, 100 mL of chloroform is added and the solution is heated for 4 hours to 40° C. After that, 2.5 mL of ethyl vinyl ether is added in one portion and stirred at 40° C. for 0.5 hours.

[0068] Afterwards, 2 g of silica gel are added and the solution is stirred for 30 minutes. The silica is then filtered using filter paper under reduced pressure (about 150 mbar). The silica is washed with 150 mL of dichloromethane at 36° C. The addition of silica gel and filtration are repeated.

[0069] Then extract the viscous solution three times with 100 mL of acid solution HCl (10%) made from 81 mL of HCl (37%) in 219 mL of DI water.

[0070] After extraction, the solution is poured into 300 mL of isopropyl alcohol to precipitate the white polymer, the mother liquor is then decanted, and the precipitate is dried in a convection oven at room temperature for 16 hours.

[0071] Example 5A This example demonstrates the synthesis of polyoctene and purification using silica gel adsorption.

[0072] In a typical experiment, a solution of 11.8 mL of cis-cyclooctene was added dropwise over 30 min to a solution of 1.3 mg of Stickycat Cl in 3 mL of chloroform.

[0073] Then, 280 mL of chloroform was added and the solution was heated to 60° C. for 12 hours. Then, 2.5 mL of ethyl vinyl ether and 10 mg of Snatchcat were added in one portion. The solution was then stirred at 40° C. for 0.5 hours.

[0074] Then, 2.0 g of silica gel was added to the solution and stirred at 40° C. for 2 hours. The silica was filtered using filter paper under reduced pressure (about 150 mbar). The silica was washed with chloroform at room temperature. The addition of 2.0 g of silica and the filtration were repeated with the filtrate.

[0075] The organic phase was then extracted three times with 100 mL of an acid solution HCl (10%) made of 81 mL of HCl (37%) in 219 mL of DI water.

[0076] After extraction, the organic solution was poured into 300 mL of isopropyl alcohol to precipitate the polymer. The liquid was then decanted. The solid was collected and dried in a convection oven at room temperature for 16 hours. (3.5 g, 35.0% yield). GPC (Mn=486.1 kDaltons, Mw=1311.2 kDaltons, D=2.7). Metal concentrations were determined using microwave digestion and ICP-MS: Al=0.83 ppm, Ti=0.32 ppm, Zn=0.37 ppm, Fe=2.42 ppm, Ru=2.40 ppm. The sum of titanium, aluminum, iron, zinc, magnesium and other metals is therefore 3.94 ppm.

[0077] Example 6: (Prophetic) This example demonstrates the synthesis of polyoctene with purification using basic extraction with tetramethylammonium hydroxide, and shows the expected M n =1100kDaltons.

[0078] In a typical experiment, a solution of 11.8 mL of cis-cyclooctene in 180 mL of chloroform is added dropwise to a solution of 6.7 mg of Stickycat Cl in 3 mL of chloroform over a period of 60 min.

[0079] Then 100 mL of chloroform was added and the solution was heated to 40° C. for 4 hours. Then 2.5 mL of ethyl vinyl ether was added in one portion and stirred at 40° C. for 0.5 hours.

[0080] Prepare a solution of NCH4OH (5%) by 30 mL of NCH4OH (25% in HO) in 120 mL of DI water. Then extract the organic phase three times with 50 mL of NCH4OH (5%) solution alternating with 50 mL of DI water.

[0081] After extraction, the solution is poured into 200 mL of IPA to precipitate the white polymer, the liquid is then decanted, and the polymer is dried in a convection oven at room temperature for 16 hours.

[0082] Example 6A This example demonstrates the synthesis of polyoctene with purification using basic extraction with tetramethylammonium hydroxide, and shows the expected M n =1100kDaltons.

[0083] In a representative experiment, a solution of 11.8 mL of cis-cyclooctene in 180 mL of chloroform was added dropwise over 60 min to a solution of 6.7 g of Stickycat Cl in 3 mL of chloroform.

[0084] Then, 100 mL of chloroform was added and the solution was heated to 60° C. for 4 hours. After that, 2.5 mL of ethyl vinyl ether and 10 mg of Snatchcat were added in one portion and the solution was stirred at 40° C. for 0.5 hours.

[0085] A solution of NCH4OH (5%) was then prepared by 30 mL of NCH4OH (25% in H2O) in 120 mL of DI water. The organic phase was then extracted three times with 50 mL of NCH4OH (5%) solution alternating with 50 mL of DI water.

[0086] After extraction, the organic solution was poured into 200 mL of IPA to precipitate the white polymer. The liquid was then decanted. The solid was collected and dried in a convection oven at room temperature for 16 hours. (4.13 g, 41.3% yield).

[0087] Metal concentrations were determined using microwave digestion and ICP-MS: Al=2.96 ppm, Mg=0.00 ppm, Ti=0.00 ppm, Zn=0.00 ppm, Fe=0.78 ppm, Ru=4.03 ppm, so the sum of titanium, aluminum, iron, zinc, and magnesium was 3.74 ppm.

[0088] Example 7: (Prophetic) This example demonstrates the synthesis of polyoctene with purification using Soxhlet extraction in IPA, and shows the expected M n =2200kDaltons.

[0089] In a typical experiment, a solution of 11.8 mL of cis-cyclooctene in 180 mL of chloroform is added dropwise to a solution of 3.3 mg of Stickycat Cl in 3 mL of chloroform over a period of 60 min.

[0090] 100 mL of chloroform is then added and the solution is heated for 4 hours to 40° C. Then 2.5 mL of ethyl vinyl ether is added in one portion and stirred at 40° C. for 0.5 hours.

[0091] The organic solution is poured into 300 mL of IPA to precipitate the white polymer.

[0092] The liquid is decanted and the white polymer is dried in a convection oven at room temperature for 10 hours. The polymer is then placed in a Soxhlet apparatus covered with a non-woven membrane and continuously extracted with IPA for 72 hours.

[0093] The polymer is then dried in a convection oven at room temperature for 16 hours.

[0094] Example 7A This example demonstrates the synthesis of polyoctene with purification using Soxhlet extraction in IPA, and shows the expected M n =2200kDaltons.

[0095] In a representative experiment, a solution of 11.8 mL of cis-cyclooctene in 180 mL of chloroform was added dropwise over 60 min to a solution of 3.2 g of Stickycat Cl in 3 mL of chloroform.

[0096] Then, 100 mL of chloroform was added and the solution was heated to 60° C. for 4 hours. After that, 2.5 mL of ethyl vinyl ether was added in one portion and the solution was stirred at 40° C. for 0.5 hours.

[0097] The organic solution was then poured into 200 mL of IPA, which allowed the white polymer to precipitate. The liquid was then decanted. The solid was collected, covered with a non-woven membrane, and introduced into a Soxhlet apparatus. The polymer was then extracted in the Soxhlet apparatus using IPA continuously for 72 hours.

[0098] The polymer was then dried in a convection oven at room temperature for 16 hours (3.6 g, 36% yield). Metal concentrations were determined using microwave digestion and ICP-MS: Al=0.00 ppm, Mg=0.00 ppm, Ti=0.26 ppm, Zn=0.00 ppm, Fe=0.00 ppm, Ru=24.24 ppm. The sum of titanium, aluminum, iron, zinc, and magnesium was therefore 0.26 ppm.

[0099] Example 8: This example demonstrates the synthesis of polyethylene by reduction of the polyoctene in Example 4.

[0100] In a typical experiment, 1.00 g of polyoctene (M n = 1100 kDaltons) was dissolved in 110 mL of xylene. The mixture was then heated to 110°C.

[0101] To the reaction mixture was added 6.78 g of p-toluenesulfonylhydrazide in one portion. Then 4.7 mL of tripropylamine was added in one portion. The reaction was heated to 150° C. and stirred at reflux for 7 hours.

[0102] It was then cooled to 135°C and poured into 300mL of IPA in one go. A white precipitate formed. The polymer was filtered through filter paper and washed with 40mL of acetone.

[0103] The polymer was dried in a convection oven for 24 hours (0.93 g, 89% yield). Melting point: 130.2°C - 134.5°C.

[0104] At 150°C 13C melt-state NMR determined a double bond concentration of 2.72% in the sample. Elemental analysis determined C = 83.68% H = 14.79% (molar ratio of H to C = 2.11).

[0105] Example 9: This example demonstrates the purification of polybutadiene by acid extraction.

[0106] In a typical experiment, 1.00 g of polybutadiene (M n = 1200 kDaltons, D = 1.18) was dissolved in 100 mL of hexane. The organic solution was extracted five times with 100 mL of an acid solution HCl (10%) made with 137 mL of HCl (37%) in 363 mL of DI water.

[0107] The solution was precipitated in 100 mL of IPA. The polymer was precipitated from the solution and filtered through filter paper. The polymer was dried in a convection oven at room temperature for 24 hours.

[0108] The polybutadiene contained a total metal concentration of <100 ppb, including titanium, aluminum, iron, zinc, and magnesium.

[0109] Example 10: This example demonstrates the synthesis of polyethylene copolymers, such as polyethylene-co-polybutylene resins, by reduction of the double bonds of polybutadiene.

[0110] In a representative experiment, 1.00 g of polybutadiene (M n = 1200 kDaltons, D = 1.18) was dissolved in 50 mL of xylene, and then 10 mg of 2,6-di-tert-butyl-4-methylphenol was added. The mixture was then heated to 110 °C.

[0111] To the reaction mixture was added 12.03 g of p-toluenesulfonylhydrazide in one portion. Then, 8.5 mL of tripropylamine was added in one portion. The reaction was heated to 150° C. and stirred at reflux for 6 hours.

[0112] The reaction mixture was cooled to 135° C. and poured into 50 mL of IPA in one portion. A white precipitate formed. The polymer was filtered using filter paper. The solid was dried in a convection oven for 24 hours. (0.83 g, 83% yield).

[0113] The polymer was redissolved in 50 mL of decahydronaphthalene at 150° C. and poured into 200 mL of IPA at room temperature. The precipitation was repeated twice. The polymer was filtered using filter paper and dried in a convection oven for 24 hours.

[0114] At 150°C 13 C melt state NMR determined a double bond concentration of 3.48% in the sample. Elemental analysis determined C=81.71% H=13.65% (molar ratio of H to C=1.99). Melting point=109.0 °C.

[0115] Example 11: (Prophetic) This example demonstrates the synthesis of polyethylene by reducing polyoctene and shows the expected M n =5600kDaltons.

[0116] In a typical experiment, 10 mg of 2,6-di-tert-butyl-4-methylphenol was dissolved in 1.00 g of polyoctene (M n = 5500 kDaltons. The mixture is then heated to 110°C.

[0117] To the reaction mixture, add 6.8 g of p-toluenesulfonyl hydrazide in one portion. Then add 4.8 mL of tripropylamine in one portion. Heat the reaction to 150° C. and stir at reflux for 6 hours.

[0118] The reaction mixture is then cooled to 135° C. and poured into 100 mL of IPA at once to precipitate the polymer. The polymer is then filtered using filter paper and the solid is dried in a convection oven for 24 hours.

[0119] Example 12: This example demonstrates the synthesis of polyoctene and purification using silica gel adsorption.

[0120] In a representative experiment, a solution of 11.8 mL of cis-cyclooctene in 180 mL of chloroform was added dropwise over 60 min to a solution of 3.2 mg of Stickycat Cl in 3 mL of chloroform.

[0121] Then, 100 mL of chloroform was added and the solution was heated to 60° C. for 4 hours. After that, 2.5 mL of ethyl vinyl ether and 10 mg of Snatchcat were added in one portion and the solution was stirred at 40° C. for 0.5 hours.

[0122] Then, 5.0 g of silica gel was added to the solution and stirred at 40° C. for 2 hours. The silica was filtered using filter paper under reduced pressure (about 150 mbar). The silica was washed with chloroform at room temperature.

[0123] The organic phase was then extracted three times with 100 mL of an acid solution HCl (10%) made of 81 mL of HCl (37%) in 219 mL of DI water.

[0124] After extraction, the organic solution was poured into 300 mL of isopropyl alcohol, which precipitated the white polymer. The liquid was then decanted. The solid was collected and dried in a convection oven at room temperature for 16 hours. (3.56 g, 35.6% yield). GPC (Mn=212.0 kDaltons, Mw=430.3 kDaltons, D=2.0). Metal concentrations were determined using microwave digestion and ICP-MS: Al=1.01 ppm, Mg=0.00 ppm, Ti=0.22 ppm, Zn=0.36 ppm, Fe=1.54 ppm, Ru=0.19 ppm. The sum of titanium, aluminum, iron, zinc, and magnesium was therefore 3.13 ppm.

[0125] Example 13: This example demonstrates the synthesis of polyoctene using Stickycat Cl that is immobilized on silica gel prior to polymerization.

[0126] In a representative experiment, Stickycat Cl was immobilized on silica gel prior to reaction. The silica gel was dried in a convection oven at 150 °C for 12 h and cooled to room temperature in a vacuum chamber before use.

[0127] A solution of 3.2 mg of Stickycat Cl in 2 mL of CHCl was added to 0.64 g of dry silica gel. The silica gel was then dried in a rotary evaporator.

[0128] A solution of 11.8 mL of cis-cyclooctene in 180 mL of chloroform was then added dropwise to the immobilized Stickycat Cl on silica gel for 60 min. The heterogeneous reaction was stirred vigorously.

[0129] Then, 100 mL of chloroform was added and the solution was heated to 60° C. for 4 hours. After that, 2.5 mL of ethyl vinyl ether and 10 mg of Snatchcat were added in one portion and the suspension was stirred at 40° C. for 0.5 hours. The silica gel was then filtered using filter paper under reduced pressure (about 150 mbar). The silica was washed with chloroform at room temperature.

[0130] The organic phase was then extracted three times with 100 mL of an acid solution HCl (10%) made of 81 mL of HCl (37%) in 219 mL of DI water.

[0131] After extraction, the organic solution was poured into 300 mL of isopropyl alcohol to precipitate the white polymer. The liquid was then decanted. The solid was collected and dried in a convection oven at room temperature for 16 hours. (2.10 g, 21.0% yield). GPC (Mn=591.2 kDaltons, Mw=1703.9 kDaltons, D=2.9).

[0132] Example 14: (Prophetic) This example demonstrates the synthesis of polyoctene using Stickycat Cl immobilized on pre-polymerized silica gel (SiliaMetS Thiol(SH) Metal Scavenger (R51030B)) and shows the expected M n=2300kDaltons.

[0133] In a typical experiment, Stickycat Cl is immobilized on silica gel (SiliaMetS Thiol (R51030B)) prior to the reaction.

[0134] A solution of 3.2 mg of StickyCat Cl in 2 mL of CHCl3 is then added to 0.64 g of silica gel (SiliaMetS Thiol (R51030B)). The silica gel is then dried in a rotary evaporator.

[0135] A solution of 11.8 mL of cis-cyclooctene in 180 mL of chloroform is then added dropwise to Stickycat Cl immobilized on silica gel (SiliaMetS Thiol (R51030B)) for 60 min and stirred vigorously.

[0136] Then, 280 mL of chloroform is added and the solution is heated for 4 hours to 40° C. After that, 2.5 mL of ethyl vinyl ether is added in one portion and stirred at 40° C. for 0.5 hours.

[0137] The silica is then filtered using filter paper under reduced pressure (about 150 mbar). The silica is washed with 150 mL of dichloromethane at room temperature.

[0138] Then extract the viscous solution three times with 100 mL of acid solution HCl (10%) made from 81 mL of HCl (37%) in 219 mL of DI water.

[0139] After extraction, the solution is poured into 300 mL of isopropyl alcohol to precipitate the white polymer, the mother liquor is then decanted, and the precipitate is dried in a convection oven at room temperature for 16 hours.

[0140] Example 15: (Prophetic) This example demonstrates the synthesis of polyoctene and its purification using a chelating resin (Puromet MTS9100), yielding the expected M n =5500kDaltons.

[0141] In a typical experiment, a solution of 11.8 mL of cis-cyclooctene is added dropwise to a solution of 1.3 mg of Stickycat Cl in 3 mL of chloroform over a period of 60 min.

[0142] Then, 100 mL of chloroform is added and the solution is heated for 12 hours to 60° C. After that, 2.5 mL of ethyl vinyl ether is added in one portion and stirred at 40° C. for 0.5 hours.

[0143] Then take 6 mL, aliquot it and add it to 0.2 g of resin (Puromet MTS9100) and stir for 24 hours.

[0144] The liquid is then decanted into another vial with 20 mL of isopropyl alcohol. The vial is agitated to allow the polymer to precipitate. The liquid is then decanted and the solid is dried in a convection oven at room temperature.

[0145] Example 16: (Prophetic) This example demonstrates the synthesis of polyoctene and its purification using an ion exchange resin (NRW160), and shows the expected M n =5500kDaltons.

[0146] In a typical experiment, a solution of 11.8 mL of cis-cyclooctene is added dropwise to a solution of 1.3 mg of Stickycat Cl in 3 mL of chloroform over a period of 60 min.

[0147] 100 mL of chloroform is then added and the solution is heated to 60° C. for 12 hours. Then, 2.5 mL of ethyl vinyl ether is added in one portion. The solution is then stirred at 40° C. for 0.5 hours.

[0148] Then take 6 mL, aliquot it and add it to 0.2 g of resin (NRW160) and stir for 24 hours.

[0149] The liquid is then decanted into another vial with 20 mL of isopropyl alcohol. The vial is agitated to allow the polymer to precipitate. The liquid is then decanted and the solid is dried in a convection oven at room temperature.

[0150] Example 17: This example demonstrates the synthesis of polyoctene using Hoveyda-Grubbs M720 initiator.

[0151] In a typical experiment, a solution of 11.8 mL of cis-cyclooctene in 180 mL of chloroform was added dropwise over 60 min to a solution of 2.8 mg of Hoveyda-Grubbs M720 initiator in 3 mL of chloroform.

[0152] Then, 100 mL of chloroform was added and the solution was heated to 60° C. for 4 hours. After that, 2.5 mL of ethyl vinyl ether was added in one portion and the solution was stirred at 40° C. for 0.5 hours.

[0153] The organic phase was then extracted three times with 100 mL of an acid solution HCl (10%) made of 81 mL of HCl (37%) in 219 mL of DI water.

[0154] After extraction, the organic solution was poured into 300 mL of isopropyl alcohol to precipitate the white polymer. The liquid was then decanted. The solid was collected and dried in a convection oven at room temperature for 16 hours. (0.75 g, 7.5% yield). GPC (Mn=31.2 kDaltons, Mw=76.4 kDaltons, D=2.5).

[0155] Aspects In a first aspect, the present disclosure provides a filter membrane comprising a polyolefin, wherein the total amount of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 4 ppm as determined by the MARS6 Microwave Acid Digestion Method Note Compendium.

[0156] In a second aspect, the present disclosure provides the membrane of the first aspect, wherein the sum of the amounts of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 3.5 ppm.

[0157] In a third aspect, the present disclosure provides the membrane of the first aspect, wherein the sum of the amounts of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 3 ppm.

[0158] In a fourth aspect, the present disclosure provides the membrane of the first aspect, wherein the sum of the amounts of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 2 ppm.

[0159] In a fifth aspect, the present disclosure provides the membrane of the first aspect, wherein the sum of the amounts of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 1 ppm.

[0160] In a sixth aspect, the present disclosure provides the membrane of the first aspect, wherein the polyolefin has less than about 1 ppm ruthenium as determined by the MARS6 Microwave Acid Digestion Method Note Compendium.

[0161] In a seventh aspect, the present disclosure provides the membrane of any one of the first to sixth aspects, wherein the polyolefin is selected from polyethylene and polyethylene-co-polybutylene.

[0162] In an eighth aspect, the present disclosure provides the membrane of any one of the first to sixth aspects, wherein the polyolefin is ultra-high molecular weight polyethylene.

[0163] In a ninth aspect, the present disclosure provides the membrane of any one of the first to eighth aspects, wherein the polyolefin has a number average molecular weight of about 330,000 to 2,200,000 Daltons.

[0164] In a tenth aspect, the present disclosure provides the membrane of any one of the first to eighth aspects, wherein the polyolefin has a number average molecular weight of about 700,000 Daltons to about 1,500,000 Daltons.

[0165] In an eleventh aspect, the present disclosure provides a polyolefin comprising: A. cis- or trans-cyclooctene is contacted with a Ru II catalyst, followed by B. Removal or extraction of Ru II catalyst, followed by C. Hydrogenation with hydrazine or hydrazide type reducing agents The present invention provides a membrane of a first aspect, which is prepared by:

[0166] In a twelfth aspect, the present disclosure provides a Ru II catalyst comprising: i. (1,3-bis(2,6-diisopropylphenyl)-4-((4-ethyl-4-methylpiperazin-1-ium-1-yl)methyl)imidazolidin-2-ylidene)(2-isopropoxybenzylidene)ruthenium(II) chloride dihydrate; ii. (1,3-Dimesityl-4-((trimethylammonio)methyl)imidazolidin-2-ylidene)dichloro(2-isopropoxybenzylidene)ruthenium(II) chloride; iii. (4-((4-ethyl-4-methylpiperazin-1-ium-1-yl)methyl)-1,3-dimesitylimidazolidin-2-ylidene)dichloro(2-isopropoxybenzylidene)ruthenium(II) chloride; iv. (1,3-dimesityl-4-((trimethylammonio)methyl)imidazolidin-2-ylidene)dichloro(2-isopropoxybenzylidene)ruthenium(II) hexafluorophosphate; and v. (1,3-Dimesityl-4-((trimethylammonio)methyl)imidazolidin-2-ylidene)dichloro(2-isopropoxybenzylidene)ruthenium(II) tetrafluoroborate The membrane according to an eleventh aspect is provided, wherein the membrane is selected from the group consisting of:

[0167] In a thirteenth aspect, the present disclosure provides the membrane of the first aspect, wherein the polyolefin is a polyethylene-co-polybutylene prepared by contacting polybutadiene with hydrogen in the presence of a hydrazide- or hydrazine-type reducing agent.

[0168] In a fourteenth aspect, the present disclosure provides a filter comprising a filter membrane comprising a polyolefin, wherein the sum of the amount of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 4 ppm as determined by the MARS6 Microwave Acid Digestion Method Note Compendium.

[0169] In a fifteenth aspect, the present disclosure provides the filter of the fourteenth aspect, wherein the sum of the amounts of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 3.5 ppm.

[0170] In a sixteenth aspect, the present disclosure provides the filter of the fourteenth aspect, wherein the sum of the amounts of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 3 ppm.

[0171] In a seventeenth aspect, the present disclosure provides the filter of the fourteenth aspect, wherein the sum of the amounts of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 2 ppm.

[0172] In an eighteenth aspect, the present disclosure provides the filter of the fourteenth aspect, wherein the sum of the amounts of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 1 ppm.

[0173] In a nineteenth aspect, the present disclosure provides the filter of the fourteenth aspect, wherein the polyolefin has less than about 1 ppm ruthenium as determined by the MARS6 Microwave Acid Digestion Method Note Compendium.

[0174] In a twentieth aspect, the present disclosure provides the filter of any one of the fourteenth to eighteenth aspects, wherein the polyolefin is selected from polyethylene and polyethylene-co-polybutylene.

[0175] In a twenty-first aspect, the present disclosure provides the filter of any one of the fourteenth to eighteenth aspects, wherein the polyolefin is ultra-high molecular weight polyethylene.

[0176] In a twenty-second aspect, the present disclosure provides the filter of any one of the fourteenth to eighteenth aspects, wherein the polyolefin has a number average molecular weight of about 330,000 to 2,200,000 Daltons.

[0177] In a twenty-third aspect, the present disclosure provides the filter of any one of the fourteenth to eighteenth aspects, wherein the polyolefin has a number average molecular weight of about 700,000 Daltons to about 1,500,000 Daltons.

[0178] In a twenty-fourth aspect, the present disclosure provides a method for removing impurities from a liquid, the method comprising contacting the liquid with a filter of any one of the fourteenth to twenty-third aspects.

[0179] Having thus described several exemplary embodiments of the present disclosure, those skilled in the art will readily appreciate that still other embodiments may be made and used within the scope of the appended claims. Many advantages of the present disclosure, which are covered by this document, have been set forth in the foregoing description. It will be understood, however, that the present disclosure is in many respects merely illustrative. The scope of the present disclosure is, of course, to be defined in the language in which the appended claims are expressed.

Claims

1. 1. A filter membrane comprising a polyolefin, wherein the total amount of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 4 ppm as determined by the MARS6 Microwave Acid Digestion Method Note Compendium.

2. 10. The membrane of claim 1, wherein the combined amount of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 3.5 ppm.

3. 10. The membrane of claim 1, wherein the combined amount of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 3 ppm.

4. 10. The membrane of claim 1, wherein the combined amount of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 2 ppm.

5. 10. The membrane of claim 1, wherein the combined amount of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 1 ppm.

6. 10. The membrane of claim 1, wherein the polyolefin has less than about 1 ppm ruthenium as determined by the MARS6 Microwave Acid Digestion Method Note Compendium.

7. The membrane according to any one of claims 1 to 6, wherein the polyolefin is selected from polyethylene and polyethylene-co-polybutylene.

8. 7. The membrane of claim 1, wherein the polyolefin is ultra-high molecular weight polyethylene.

9. The membrane of any one of claims 1 to 8, wherein the polyolefin has a number average molecular weight of about 330,000 to 2,200,000 Daltons.

10. 9. The membrane of any one of claims 1 to 8, wherein the polyolefin has a number average molecular weight of about 700,000 Daltons to about 1,500,000 Daltons.

11. The polyolefin is A. Cis or trans-cyclooctene is contacted with Ru II catalyst, followed by B. Removal or extraction of the Ru II catalyst, followed by C. Hydrogenation with hydrazine- or hydrazide-type reducing agents The membrane of claim 1 prepared by:

12. The Ru II catalyst is i. (1,3-bis(2,6-diisopropylphenyl)-4-((4-ethyl-4-methylpiperazin-1-ium-1-yl)methyl)imidazolidin-2-ylidene)(2-isopropoxybenzylidene)ruthenium(II) chloride dihydrate; ii. (1,3-dimesityl-4-((trimethylammonio)methyl)imidazolidin-2-ylidene)dichloro(2-isopropoxybenzylidene)ruthenium(II) chloride; iii. (4-((4-ethyl-4-methylpiperazin-1-ium-1-yl)methyl)-1,3-dimesitylimidazolidin-2-ylidene)dichloro(2-isopropoxybenzylidene)ruthenium(II) chloride iv. (1,3-dimesityl-4-((trimethylammonio)methyl)imidazolidin-2-ylidene)dichloro(2-isopropoxybenzylidene)ruthenium(II) hexafluorophosphate; and v. (1,3-dimesityl-4-((trimethylammonio)methyl)imidazolidin-2-ylidene)dichloro(2-isopropoxybenzylidene)ruthenium(II) tetrafluoroborate The membrane of claim 11 , wherein the membrane is selected from:

13. 2. The membrane of claim 1, wherein the polyolefin is a polyethylene-co-polybutylene prepared by contacting polybutadiene with hydrogen in the presence of a hydrazide or hydrazine type reducing agent.

14. 1. A filter comprising a filter membrane comprising a polyolefin, wherein the combined amount of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 4 ppm as determined by the MARS6 Microwave Acid Digestion Method Note Compendium.

15. 15. The filter of claim 14, wherein the combined amount of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 3.5 ppm.

16. 15. The filter of claim 14, wherein the combined amount of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 3 ppm.

17. 15. The filter of claim 14, wherein the combined amount of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 2 ppm.

18. 15. The filter of claim 14, wherein the combined amount of titanium, aluminum, iron, zinc, and magnesium in the polyolefin is less than about 1 ppm.

19. 15. The filter of claim 14, wherein the polyolefin has less than about 1 ppm ruthenium as determined by the MARS6 Microwave Acid Digestion Method Note Compendium.

20. A filter according to any one of claims 14 to 18, wherein the polyolefin is selected from polyethylene and polyethylene-co-polybutylene.

21. 19. A filter according to any one of claims 14 to 18, wherein the polyolefin is ultra-high molecular weight polyethylene.

22. The filter of any one of claims 14 to 18, wherein the polyolefin has a number average molecular weight of about 330,000 to 2,200,000 Daltons.

23. The filter of any one of claims 14 to 18, wherein the polyolefin has a number average molecular weight of about 700,000 Daltons to about 1,500,000 Daltons.

24. 24. A method for removing impurities from a liquid, comprising contacting the liquid with a filter according to any one of claims 14 to 23.